PENGABDIAN KEPADA MASYARAKAT SISTEM INFORMASI KEGIATAN TERPADU (SIKAT) REMAJA SINODE GMIM - Edmond, Komansilan; Arnetha, Raintung (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2020)
Abstract The GMIM Synod Youth Services Commission is part of the ministry of the Evangelical Christian Church in Minahasa in the Province of North Sulawesi. In its service under the auspices of the Evangelical Christian Church in Minahasa (GMIM) the Youth Services Commission specializes in providing services to teenagers aged 12-16 years according to the administration of the GMIM church. With the current technology, the GMIM Synod Youth Services Commission has developed a sistem to assist the implementation of each activity or program implemented in the form of an Integrated Activity Information Sistem (SIKAT). The development of this Information Sistem has not been widely known by adolescents and youth coaches so that in practice there are still congregations or coaches who have not used this sistem. Therefore, the development of this information sistem needs to be followed by training on how to use an integrated activity information sistem (SIKAT), so that in the implementation of the GMIM Synod Youth activities all can be recorded properly through the sistem that has been built. Activity Output: Integrated Information Sistem Application for GMIM Synod Teens.